Digital Marketing of Commercial Complementary Foods in Australia: An Analysis of Brand Messaging. - Dearlove, Trish; Begley, Andrea; Scott, Jane; Devenish-Coleman, Gemma (MDPI AG, 2021)
The digital marketing of commercial complementary foods (CCF) is an emerging area of concern in Australia. Although research into traditional methods has identified a range of problems, the marketing and messaging strategies employed within digital spaces have gone largely unscrutinized. This study sought to examine the methods used by CCF manufacturers to promote Australian baby foods and brands in a digital space. A multiple step approach was used to assess the CCF brands available in major Australian retailers, the social media platforms they used, and to thematically analyze the text and visual messages contained in posts published over a three-month period. Of the 15 brands identified, 12 had a digital presence, and all of these used Facebook. Four themes emerged from an analysis of 216 Facebook posts; (1) general product attributes, (2) socially desirable attributes (which included messaging related to taste (41%), self-feeding (29%) and fun (19%)), (3) concern-based attributes (including organic status (40%), age targets (39%) and additive-/allergen-free status (18%)) and (4) health-focused attributes (which included messaging related to healthy/nutritious ingredients (45%), and child development/growth (15%). Messages contained in Facebook posts were mostly positive brand/product aspects (Themes 1 and 2) or parental concern-based aspects (Theme 3 and 4). These themes match previous analyses of marketing content in traditional media and should be closely monitored due to the personalized nature of consumer social media interactions.